Response of foliar metabolism in mature trees of Quercus pubescens and Quercus ilex to long-term elevated CO 2 - Tognetti, Roberto; Johnson, J D (Environmental and Experimental Botany, 1998)
Long-term effects on and adaptations of the carbon physiology of long-lived trees exposed to increasing atmospheric levels of CO2 are unknown. We compared two indigenous Quercus species, Q. ilex and Q. pubescens, growing in a natural CO2 spring located in central Italy and at a nearby control site. In May, 1995 photosynthetic rate at least doubled when measured with supplemental CO2 in both species and sites. Dark respiration was much higher at the CO2 spring site in both species. Foliar sugar and starch concentrations in Q. ilex exhibited signiﬁcant site and diurnal differences (May and September). In July, 1995 there was little difference in the water potential values of the measured trees at the different sites over the diurnal period. Photosynthetic rate was higher for both species in the CO2 spring, particularly in the early morning and late afternoon. Mid-day stomatal closure reduced photosynthesis to similar levels. In the morning leaf conductance and transpiration were generally lower in the CO2 spring trees, contributing to higher instantaneous water use efﬁciency for both species. Isoprene emission rates were higher in Q. pubescens trees growing in the CO2 spring. The maximum difference between control and CO2 spring trees occurred in late afternoon. In contrast, Q. ilex exhibited isoprene emission near background level. Foliage and branch carbon and nitrogen status showed increased concentrations of starch and tannins in Q. ilex and of soluble sugars in Q. pubescens in the elevated CO2 environment, while nitrogen concentration decreased in both species. Wood gravity increased 6 and 3% in Q. ilex and Q. pubescens, respectively, growing in the CO2 spring. Q. ilex exhibited afternoon recovery of water potential compared to Q. pubescens which had better night-time recovery. Q. ilex and Q. pubescens exposed to elevated CO2 for prolonged periods exhibit different mechanisms for dealing with additional reduced carbon and do maintain an altered carbon physiology, even in midst of the region’s characteristic summer drought
Keywords: Elevated CO2; Gas exchange; natural CO2 springs; Quercus; Secondary compounds